2014
DOI: 10.1371/journal.pone.0110162
|View full text |Cite
|
Sign up to set email alerts
|

The Cytochrome P450 Epoxygenase Pathway Regulates the Hepatic Inflammatory Response in Fatty Liver Disease

Abstract: Fatty liver disease is an emerging public health problem without effective therapies, and chronic hepatic inflammation is a key pathologic mediator in its progression. Cytochrome P450 (CYP) epoxygenases metabolize arachidonic acid to biologically active epoxyeicosatrienoic acids (EETs), which have potent anti-inflammatory effects. Although promoting the effects of EETs elicits anti-inflammatory and protective effects in the cardiovascular system, the contribution of CYP-derived EETs to the regulation of fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 44 publications
3
73
2
Order By: Relevance
“…Multiple preclinical studies have also demonstrated that CYP epoxygenase expression and EET biosynthesis are suppressed in the presence of pathological infl ammation. Notably, hepatic CYP epoxygenase expression, hepatic CYP epoxygenase metabolic function, and plasma EET levels were suppressed in an atherogenic diet mouse model of infl ammatory fatty liver disease ( 29 ). In contrast, no changes in sEH expression or EET hydrolysis were observed.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple preclinical studies have also demonstrated that CYP epoxygenase expression and EET biosynthesis are suppressed in the presence of pathological infl ammation. Notably, hepatic CYP epoxygenase expression, hepatic CYP epoxygenase metabolic function, and plasma EET levels were suppressed in an atherogenic diet mouse model of infl ammatory fatty liver disease ( 29 ). In contrast, no changes in sEH expression or EET hydrolysis were observed.…”
Section: Discussionmentioning
confidence: 91%
“…Free eicosanoid metabolite concentrations were quantified from mouse and human samples using a targeted liquid chromatography-tandem mass spectrometry (LC/MS/MS) method with optimized sensitivity and specificity for EET quantification, as previously described (11, 12, 20). Briefly, plasma/serum (0.25 mL) and homogenized liver (20 mg) and eWAT (50 mg) tissue were diluted in 0.1% acetic acid/5% methanol solution containing 0.009 mM butylated hydroxytoluene (BHT), and internal standards were added.…”
Section: Methodsmentioning
confidence: 99%
“…Due to significant correlations among the EET and DHET regioisomers (11, 12, 20), the sum of the EET regioisomers (sum EETs) and DHET regioisomers (sum DHETs) were calculated to minimize redundancy. The sum of the EET and DHET regioisomers (sum EETs+DHETs) and the ratio of 14,15-EET to 14,15-DHET (14,15-EET:14,15-DHET ratio) were calculated as biomarkers of CYP epoxygenase and sEH metabolic function, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity was significantly correlated with low plasma EET levels in a clinical study (Theken et al, 2012). Multiple studies have associated increased EET levels with a reduction in inflammation and other symptoms of disease in rodent models of obesity and diabetes (Fleming, 2014), and fatty liver disease Schuck et al, 2014). CYP epoxygenase expression in locations such as liver, endothelial cells, pancreas, and mesenchymal stem cells is relevant to these activities.…”
Section: Inflammation and Metabolic Syndromementioning
confidence: 99%